A Race Between Economic Growth and Carbon Emissions: How Will the CO2 Emission Reach the Peak in Transportation Industry? - Wu, Ya; Zhou, Yitong; Liu, Yin; Liu, Jiawei (Frontiers in Energy Research, 2022)
Promoting carbon emissions of the transportation industry to reach the peak as soon as possible is an effective way to control carbon emissions in China. Combined with the logarithmic mean Divisia index (LMDI) model and the Tapio decoupling model, this paper tries to predict and analyze the time, path, and quality of carbon peaking in the transportation industry in China and its eastern, central, and western regions. The research shows the following: 1) Under the “benchmark scenario,” the transportation industry in China and its three regions will not achieve the international commitment of achieving peak carbon emissions by 2030. 2) Under the “radical scenario,” the peak time of China’s transportation industry can be reached in 2027, which is 5 years earlier, 10% peak value lower than that in the “benchmark scenario.” In that scenario, in transportation industry, the eastern region will reach the carbon peak in 2025 and the central and western regions will both reach the carbon peak in 2028. By then, the peak quality of carbon emissions will be better than that under the “benchmark scenario” in transportation industry. This paper can provide theoretical support for promoting carbon emission reductions and carbon peaking in China’s transportation industry.